Human herpesvirus 6B induces phosphorylation of p53 in its regulatory domain by a CK2- and p38-independent pathway - Øster, B.; Bundgaard, B.; Hupp, T. R.; Höllsberg, P. (Journal of General Virology, 2008)
Here, we demonstrate that human herpesvirus 6B (HHV-6B) infection upregulates the tumour suppressor p53 and induces phosphorylation of p53 at Ser392. Interestingly, phosphorylation at the equivalent site has previously been shown to correlate with p53 tumour suppression in murine models. Although the signalling pathways leading to Ser392 phosphorylation are poorly understood, they seem to include casein kinase 2 (CK2), double-stranded RNA-activated protein kinase (PKR), p38 or cyclin-dependent kinase 9 (Cdk9). By using column chromatography and in vitro kinase assays, CK2 and p38, but not PKR or Cdk9, eluted in column fractions that phosphorylated p53 at Ser392. However, treatment of cells with neither the CK2 and Cdk9 inhibitor 5,6-dichloro-1-β-d-ribofuranosylbenzimidazole (DRB) nor p38 kinase inhibitors reduced HHV-6B-induced Ser392 phosphorylation significantly. Knockdown of the CK2β subunit or p38α by small interfering RNA had no effect on HHV-6B-induced phosphorylation of p53 at Ser392. Thus, HHV-6B induces p53 Ser392 phosphorylation by an atypical pathway independent of CK2 and p38 kinases, whereas mitogen-activated protein (MAP) kinase signalling pathways are involved in viral replication.